Flavonoids influence key rhizocompetence traits for early root colonization and PCB degradation potential of Paraburkholderia xenovorans LB400 - Ghitti, Elisa; Rolli, Eleonora; Vergani, Lorenzo; Borin, Sara (Frontiers in Plant Science, 2024)
Flavonoids are among the main plant root exudation components and, besides their role in symbiosis, they can broadly affect the functionality of plant-associated microbes: in polluted environments, for instance, flavonoids can induce the expression of the enzymatic degradative machinery to clean-up soils from xenobiotics like polychlorinated biphenyls (PCBs). However, their involvement in root community recruitment and assembly involving non-symbiotic beneficial interactions remains understudied and may be crucial to sustain the holobiont fitness under PCB stress. By using a set of model pure flavonoid molecules and a natural blend of root exudates (REs) with altered flavonoid composition produced by Arabidopsis mutant lines affected in flavonoid biosynthesis and abundance (null mutant tt4, flavonoid aglycones hyper-producer tt8 and flavonoid conjugates hyper-accumulator ttg), we investigated flavonoid contribution in stimulating rhizocompetence traits and the catabolic potential of the model bacterial strain for PCB degradation Paraburkholderia xenovorans LB400.Flavonoids influenced the traits involved in bacterial recruitment in the rhizoplane by improving chemotaxis and motility responses, by increasing biofilm formation and by promoting the growth and activation of the PCB-degradative pathway of strain LB400, being thus potentially exploited as carbon sources, stimulating factors and chemoattractant molecules. Indeed, early rhizoplane colonization was favored in plantlets of tt8 Arabidopsis mutant and reduced in ttg line. Bacterial growth was promoted by the REs of mutant lines tt4 and tt8 under control conditions and reduced upon PCB-18 stress, showing no significant differences compared to the WT and ttg, indicating that unidentified plant metabolites could be involved. PCB stress presumably altered Arabidopsis root exudation profile, although a sudden 'cry-for-help' response to recruit strain LB400 was excluded and flavonoids appeared not to be the main determinants. In the in vitro plant-microbe interaction assays, plant growth promotion and PCB resistance promoted by strain LB400 seemed to act through flavonoid-independent mechanisms without altering bacterial colonization efficiency and root adhesion pattern.This study further contributes to elucidate the vast array of functions provided by flavonoids in orchestrating the early events of PCB-degrading strain LB400 recruitment in the rhizosphere and to support the holobiont fitness by stimulating the catabolic machinery involved in xenobiotics decomposition and removal.